Effects of stimulation conditions and subcutaneous tissue properties on acupressure-induced changes in blood circulation of human tendons - Ayaka Yasuda; Shuhei Sasajima; Takehiro Kosaka; Soushi Mino; Keitaro Kubo (Japanese Society of Physical Fitness and Sports Medicine, 2023)
The purpose of this study was to investigate the effects of stimulation conditions (pressing force and frequency) and subcutaneous tissue properties (thickness and hardness) on the changes in tendon blood circulation caused by acupressure. Before and after acupressure, blood circulation of the Achilles tendon was measured using red laser lights. Acupressure was applied to the Achilles tendon for 3-min under three conditions. The following four conditions (including no stimulation condition) with different combinations of pressing forces and frequencies were established: 1) 50N and 1.5Hz, 2) 25N and 3.0Hz, 3) 25N and 1.5Hz, and 4) no stimulation. In addition, the thickness and hardness of subcutaneous tissue at the acupressure-stimulated site were measured. The change in total hemoglobin (corresponding to blood volume) showed a significant main effect of condition, but the effects of time and the interaction between conditions and time were not significant. On average, the most significant increase in tendon blood volume was observed in the 50N and 1.5Hz condition, although the post-hoc test showed no significant difference. The subcutaneous tissue thickness and hardness were not significantly correlated with tendon blood volume changes after stimulation in any of the three conditions. In conclusion, the present results indicate that acupressure under the conditions of pressing force 50N and frequency 1.5Hz changed tendon blood circulation the most, though not based on exact statistical results. Furthermore, the subcutaneous tissue thickness and hardness (including tendon) have no effect on tendon blood circulation induced by stimulation.